Dexamethasone and 5% NaCl Solution Induce Hypertension in Sparangue dawly Male Rats - Imam Syafi'i; Fadlina Chany Saputri; Berna Elya (Universitas Pakuan, 2022)
High blood pressure can be caused by excess salt intake Dexamethasone is a potent anti-inflammatory drug, but the long-term administration can cause hypertension. This study aims to determine the accurate time and dose that cause hypertension in rat models by administration of a combination of dexamethasone and 5% NaCl solution. The control group was administrated with aquadest orally, 3 test groups were administrated with dexamethasone at a doses of 0.02mg/kg BW, 0.03mg/kg BW, and 0.5mg/kg BW intraperitonially (i.p) for 28 days. A 5% NaCl solution were administrated instead of drinking water to the test group. Blood pressure and body weight were measured weekly for 28 days. Results of the study show that Dexamethasone at a dose of 0.02mg/kg BW caused hypertension on day-28 where the rats blood pressure increase to 148mmHg/103mmHg (±1.9/±3.1) (P0.05) compared to control rats and the weight decline by 90 grams. Dexamethasone 0.03mg/kg BW caused hypertension on day-21, with the increase of rats blood pressure at144mmHg/101mmHg (±2,6/±3.2) (P0.05) compared to control and the weight decrease by 83 grams. Dexamethasone 0.5mg/kg BW caused hypertension on day-7, the rats blood pressure rise to 146mmHg/103mmHg (±1.6/1.9) (P0.05) compared to control and the weight decrease by 69 grams. As conclusion, Dexamethasone at dose of 0.5mg/kg BW and NaCl 5% cause hypertension faster on day 14 compared to dexamethasone at dose of 0.02mg/kg BW and NaCl 5% which cause hypertension slower after 28 days of administration.